Intensitas Serangan Dan Fluktuasi Populasi Wereng Batang Coklat Nilaparvata lugens Dengan Beberapa Teknik Pengendalian Pada Tanaman Padi - Sekar Hanum Raihan; Lutfi Afifah; Sulistyo Sidik Purnomo; Budi Irfan (AGRICA, 2023)
The brown planthopper is an important pest in rice cultivation which acts as a vector for viruses that cause grass stunt and hollow stunt disease which can cause rice plants to die or reduce production to the detriment of farmers. This study aimed to obtain a pest control technique capable of suppressing the population and intensity of brown planthopper attacks on rice plants. This study is an experimental study using single-factor Randomized Block Design (RBD) with 4 treatments and 6 replications: C (Control); CC (Combination Control); BC (Biointensive Control); SC (Synthetic Control). The analysis results obtained showed that the SC treatment gave the lowest attack intensity value of 0.00% - 28.67% with a total population of 0 - 89 individuals followed by CC (1.33% - 44.67%) with a total population of 2-114 individuals, BC (2.00%-46%) with a total population of 3 - 103 individuals, and C (2.00% -45.33%) with a total population of 3 - 102 individuals. Synthetic control can be recommended as an alternative pest control technique in reducing the intensity of brown planthopper attacks.